Bodily-tactile early intervention for a mother and her child with visual impairment and additional disabilities: a case study - Peltokorpi Sini; Salo Saara; Nafstad Anne; Hart Paul; Tuomikoski Elsa; Laakso Minna (TAYLOR & FRANCIS LTD, 2022)
Purpose Congenital visual impairment and additional disabilities (VIAD) may hamper the development of a child's communication skills and the quality of overall emotional availability between a child and his/her parents. This study investigated the effects of bodily-tactile intervention on a Finnish 26-year-old mother's use of the bodily-tactile modality, the gestural and vocal expressions of her one-year-old child with VIAD, and emotional availability between the dyad. Materials and methods Mixed methods were used in the video analysis. The child's and his mother's bodily-tactile and gestural expressions were analyzed using a coding procedure. Applied conversation analysis was used to further analyse the child's emerging gestural expressions in their sequential interactive context. Emotional availability scales were used to analyze the emotional quality of the interaction. Results The results showed that the mother increased her use of the bodily-tactile modality during the intervention, especially in play and tactile signing. The child imitated new signs and developed new gestural expressions based on his bodily-tactile experiences during the intervention sessions. His vocalizations did not change. Emotional availability remained stable. Conclusions The case study approach allowed the in-depth investigation of the components contributing to the emergence of gestural expressions in children with VIAD.